(untitled) (Moderation: Journal of Islamic Studies Review, 2023)
This research is motivated by the difference between the theory of the concept of nazhar in Islam and the concept of nazhar in mubarakah marriages at the Hidayatullah Islamic Boarding School, balikpapan, where the concept of nazhar in mubarakah marriage does not only look at the woman who will be proposed to directly, but there are criteria that are seen in terms of non-physical so that this is what is considered in the matchmaking process. Therefore, researchers are interested in digging up information and knowing more deeply about the concept of nazhar in Islam and the wisdom in its law, with the concept of nazhar in mubarakah marriages, so that the similarities and differences can be examined and later the concept of nazhar in mubarakah marriages will be reviewed for conformity with Islamic law. This research is descriptive-analytical in nature which describes the concept of nazhar in mubarakah marriages, then analyzes its suitability with Islamic law based on the formulation of the problem and research objectives. The locus of this research is the Hidayatullah Islamic Boarding School, Balikpapan. The data collection technique in this study was by direct interviews with respondents, as well as studying documents about the mubarakah marriage process. Respondents in this study were members of the steering committee (steering committee), organizing committee (organizing committee) and mubarakah wedding participants, as well as the people involved in the event. From the results of this study, several aspects were found for the matchmaking process, namely; Religion and institutional idealism, educational background, ethnicity, appearance or physique and wealth. Therefore, researchers did not find a significant difference between the theory of the concept of nazhar in Islam and the concept of nazhar in Mubarakah marriages, because the concept is still based on sharia principles even in accordance with the purpose of the sharia being carried out (maqasidus sharia), and the existence of this nazhar concept in marriage mubarakah is intended to avoid post-marriage conflict, so that the integrity of the household is deemed necessary as the actualization of positive values and in accordance with the goals of marriage